Peningkatan Ketrampilan Menulis Teks Eksposisi dengan Menggunakan Metode Brainwriting - Budiani, Sri Avrianita (Paedagogie, 2018)
This research is a classroom action research conducted in two cycles, starting from (1) planning, (2) implementation, (3) evaluation, and (4) reflection. The purpose of this research is to improve students' skill of class X.IIK MAN Salatiga in writing exposition text using brainwriting method. The subjects of this study are students of class X.IIK MAN Salatiga as many as 40 students consisting of 15 men and 25 women. Data collection techniques used are test and non-test techniques. The results of this study indicate that the students’ writing skills of exposition text have a significant improvement after applied the method of brainwriting in the learning process. This is evidenced by the average score in the first cycle of 69.80 with the category ‘not complete’ and increased to 83.08 on the second cycle with the category ‘due diligence’.